(3QSGdI ajeG LGA aj GdYjfs
(3ChdgG (B:s
(3UM Yf QShd Gddg Udi Gddg Ydjg hSde Cfg bGd (B" (3GdYjf Mb GdYjf Mb GdYjf Mb (B" s
(3BNQgG (B:s
(3abGeG jdYHGf Hjf jOjg abGd GdfHi Udi Gddg Ydjg hSde YhPhG CfaSce hfSGAce hChdGOce HgDdGA GdcdeGJ GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs